A carência e a falência dos púlpitos no movimento evangélico brasileiro: uma visão panorâmica - Padilha, Adilmar Luiz Martins (2010)
We live in times of change in man's relationship with the Gospel. This study aims to show some distortions that have proliferated in the media called evangelicals, shown for both, some of the elements that have worked together to gradually emptying and homiletic preaching from the pulpits. In this sense, the Pentecostal Movement is marked by the absence of doctrinal or hermeneutical characteristics, which are influenced by unfair foreign to the Word of God. You can t say that the blame for the failure of homilies from the pulpit is only given to Neopentecostais, however, they possess a reductionist view of God, that limit to three areas: financial prosperity, health and personal achievements, so we prioritize the search for human pleasure, a flattening of earthly achievements. In this context, however, there are still examples of individuals who continue giving up everything to devote his life to the Lord and the Gospel, of which mostly are anonymous. These are maintaining the integrity and fairness of the Gospel through the ages. It follows, then, that the Gospel does not wither away as people imbued with the true mission to continue giving their lives for the sake of souls who have not bowed or even heard of the true Christ.